The Solid Phase Distribution and Bioaccessibility of Arsenic, Chromium, and Nickel in Natural Ironstone Soils in the UK - Joanna Wragg; Mark Cave; Sean Gregory (Applied and Environmental Soil Science)
Thirty soil samples (12 residential gardens and 18 allotments) were collected from the Cherwell District of north Oxfordshire in south-central England. The underlying parent geology of the area is dominated by Jurassic ironstone. The samples were analysed for their total contents of As, Cr, and Ni by X-ray fluorescence spectroscopy and for the bioaccessible fractions of these elements using a physiologically based extraction test. Four soils (two residential soils and two allotment soils) were chosen for further determination of their element solid phase distribution. The study showed that whilst total concentrations of As, Cr, and Ni are elevated due to the soil parent material, the bioaccessibility test showed that only a small proportion of the total concentration is available for absorption into the human body (<15%). The sequential extraction test showed that the nonmobile forms of the elements are strongly sorbed on to iron oxides. Parent material geology has a significant effect on the total element concentrations and the bioaccessibility of potentially harmful element (PHE). Land use does not show such a large effect but the allotment bioaccessibility data show a bigger spread and possibly higher values for As and Cr which may be due to agronomic (cultivation) practices such as addition of fertilisers and organic matter.